2019
DOI: 10.1002/lary.28270
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Versus Open Resection of Non‐Squamous Cell Carcinoma Sinonasal Malignancies

Abstract: Objective Non‐squamous cell carcinoma (non‐SCC) variants of sinonasal cancer are rare cancers which are optimally managed with complete surgical resection. This study aims to assess the impact of surgical approach on outcomes by comparison of cases managed with open versus endoscopic resection. Methods The National Cancer Database 2004–2015 datasets were queried for all cases of non‐SCC initially managed with definitive surgery. Patients were grouped according to surgical approach (endoscopic vs. open) and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…Different studies comparing the oncological results between the transfacial and endoscopic approaches have shown similar results in terms of survival [46,[50][51][52]. For example, the NCDB study by Povolotskiy et al, which included 1595 patients with non-squamous sinonasal carcinoma, found an overall survival of 65.2% in patients treated by endoscopy and 65.4% in patients treated externally (p = 0.59) [52]. It should be noted that the analysis of the literature was limited for a long time by the fact that the published studies were retrospective, with, in the first series, tumors of an earlier stage in the group of patients operated by endoscopic approach compared to those operated by external approach.…”
Section: Oncological Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Different studies comparing the oncological results between the transfacial and endoscopic approaches have shown similar results in terms of survival [46,[50][51][52]. For example, the NCDB study by Povolotskiy et al, which included 1595 patients with non-squamous sinonasal carcinoma, found an overall survival of 65.2% in patients treated by endoscopy and 65.4% in patients treated externally (p = 0.59) [52]. It should be noted that the analysis of the literature was limited for a long time by the fact that the published studies were retrospective, with, in the first series, tumors of an earlier stage in the group of patients operated by endoscopic approach compared to those operated by external approach.…”
Section: Oncological Resultsmentioning
confidence: 86%
“…Endoscopic surgery, therefore, reduces this time, reducing the delay to 15 days between diagnosis and radiotherapy compared to craniectomy surgery, in a series of 168 patients matched on the National Cancer DataBase (NCDB) [49]. Different studies comparing the oncological results between the transfacial and endoscopic approaches have shown similar results in terms of survival [46,[50][51][52]. For example, the NCDB study by Povolotskiy et al, which included 1595 patients with non-squamous sinonasal carcinoma, found an overall survival of 65.2% in patients treated by endoscopy and 65.4% in patients treated externally (p = 0.59) [52].…”
Section: Oncological Resultsmentioning
confidence: 99%
“…Surgical margin status is regarded as an independent risk factor for recurrence and survival [20,27,28] . Some scholars have found that these two surgical groups are similar with regard to negative surgical margin rate, at approximately 70-80% [19,21,22,29,30] . Regretfully, the status of the surgical margin cannot be compared between the two surgical groups in our series because some patients in the open surgery group underwent preoperative radiotherapy, promoting a higher R0 resection rate [30,31] .…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have conducted studies comparing open and endoscopic approaches [ 19 , 22 , 24 , 48 , 101 , 113 – 115 ]. Higgins et al [ 22 ] conducted a systematic review with a pooled-data analysis to compare outcomes of endoscopic vs. craniofacial resection of SNMT.…”
Section: Comparing Outcomes Of Open and Endoscopic Approaches Revisitedmentioning
confidence: 99%